2016
DOI: 10.1590/s1806-37562015000000192
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the severity of critically ill patients and clinical predictors of bronchial aspiration

Abstract: Objective: To determine whether the severity of non-neurological critically ill patients correlates with clinical predictors of bronchial aspiration. Methods: We evaluated adults undergoing prolonged orotracheal intubation (> 48 h) and bedside swallowing assessment within the first 48 h after extubation. We collected data regarding the risk of bronchial aspiration performed by a speech-language pathologist, whereas data regarding the functional level of swallowing were collected with the American Speech-Langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
0
11
0
4
Order By: Relevance
“…The study sample consisted of 295 participants. For the purposes of statistical analysis, the patients were grouped according to the ASHA NOMS score obtained in the initial speech-language evaluation as follows: levels 1 and 2 -ASHA1 (51 participants); levels 3, 4 and 5 -ASHA2 (96 participants); and levels 6 and 7 -ASHA3 (148 participants) 12,13 . Table 1 shows the comparison of demographic variables and GCS scores between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…The study sample consisted of 295 participants. For the purposes of statistical analysis, the patients were grouped according to the ASHA NOMS score obtained in the initial speech-language evaluation as follows: levels 1 and 2 -ASHA1 (51 participants); levels 3, 4 and 5 -ASHA2 (96 participants); and levels 6 and 7 -ASHA3 (148 participants) 12,13 . Table 1 shows the comparison of demographic variables and GCS scores between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…In our hospital, the risk of bronchoaspiration is determined based on the Speech-Language Dysphagia Risk Evaluation Protocol (DREP) 13 . Based on the study by Medeiros et al 14 The results indicated a statistically significant difference for the following variables: age, mortality, OTI days, number of speech therapy sessions and days to hospital discharge. Statistical analysis by the Kruskal-Wallis test indicated that patients with ASHA3 functional deglutition level were significantly younger when compared with the other groups (ASHA1 -p=0.001; ASHA2 -p=0.014).…”
Section: Methodsmentioning
confidence: 97%
“…Therefore, dysphagia has a significant impact on hospital stay time, which is an indicator of poor prognosis 13 . In addition, the literature also indicates that age (>55 years) and the presence of dysphagia after extubation increase mortality during hospitalization 11,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In general medical populations, the overall burden of dysphagia on public health care system is considered high. Dysphagia-associated complications include increased risk for aspiration, aspiration-induced pneumonia [6, 926], delayed resumption of oral intake/malnutrition [3, 10–13, 27, 28], decreased quality of life [21, 27], prolonged ICU and/or hospital length of stay [3, 8, 11, 14, 29], and increased morbidity and mortality [3, 6, 8, 9, 13, 27, 3033].…”
Section: Introductionmentioning
confidence: 99%